Teaching Sociolinguistics with Dialectometry to Identify Language in Contact of Certain Region - Vina Fathira (Universitas Lancang Kuning, 2016)
The dialectometry is one way in analyzing language in contact focusing on the similarities anddifferences of language. Linguistics Students in Indonesia were expected to be able in identifying the languagein contact. This study sees Rokan Hulu object to study as one of interesting regencies in Riau Province inIndonesia lies among 3 regions having 3 different ethnics’ languages such as: West Sumatra Province withMinangese language, North Sumatra Province with Bataknese/Mandailing language, and Bengkalis Regencywith Malay language. This study aims at identifying language in contact of using dialectometry. Qualitativemethod employed in this study followed by quantitative method in calculating data. This study was conductedin Rokan Hulu Regency by 21 observation spots. In collecting data, questionnaire of Swadesh consisting of200 words had been recorded, transcribed in phonetic transcription, and drawn in language mapping. Theresult showed that the identification of language in contact by using dialectometry calculation was easy toidentify language in contact. Then, the language in contact in Rokan Hulu Regency was dominated by Malaylanguage and Mandailing language. It means that, there is only one language in Rokan Hulu Regency calledMalay-Mandailing language.